2012
DOI: 10.1002/art.34595
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis and disease‐related autoantibodies in individuals at increased risk of rheumatoid arthritis

Abstract: Objective To examine the relationship of Porphyromonas gingivalis to the presence of autoantibodies in individuals at risk of rheumatoid arthritis (RA). Methods Study participants included the following: 1) a cohort enriched in subjects with HLA–DR4 and 2) subjects at risk of RA by virtue of having a first‐degree relative with RA. None of the study subjects satisfied the American College of Rheumatology 1987 classification criteria for RA. Autoantibodies measured included anti–citrullinated protein antibody (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 201 publications
(189 citation statements)
references
References 44 publications
10
168
2
9
Order By: Relevance
“…Porphyromonas gingivalis, the most common pathogen of periodontitis, expresses a PAD-like enzyme that is capable of citrullinating host proteins (6,7). Several epidemiological studies have suggested an association between periodontitis and risk of developing ACPA or RA (8)(9)(10). In addition, a functional haplotype stabilizing the mRNA from padi4, the gene encoding PAD4, is associated with a higher risk of RA and the presence of ACPA in RA patients (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Porphyromonas gingivalis, the most common pathogen of periodontitis, expresses a PAD-like enzyme that is capable of citrullinating host proteins (6,7). Several epidemiological studies have suggested an association between periodontitis and risk of developing ACPA or RA (8)(9)(10). In addition, a functional haplotype stabilizing the mRNA from padi4, the gene encoding PAD4, is associated with a higher risk of RA and the presence of ACPA in RA patients (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed a reduction of the severity of active RA when the accompanying PD was successfully treated (15,16). In addition, enhanced Ab titers against Porphyromonas gingivalis, the major causative agent of periodontitis, have been detected in serum of patients with RA as well as in individuals at increased risk of developing RA (17,18).…”
mentioning
confidence: 98%
“…Additionally, there is evidence that PAD auto- No difference found in anti-P gingivalis levels between RA patients and controls. Mikuls et al (68) Anti-P gingivalis antibodies Higher levels of anti-P gingivalis antibodies in at-risk individuals with RA autoantibodies compared to those seronegative for autoantibodies. Lappin et al (21) Anti-CCP antibodies Patients with PD had higher anti-CCP levels than healthy controls; significant reductions in anti-CCP and anti-P gingivalis titers seen after PD treatment.…”
Section: Localized Autoimmunity: Initiating Events At Mucosal Surfacesmentioning
confidence: 99%